Studies on qualitative phytochemical analysis and biological activities of carica papaya leaves / Halimatussaadiah Sazali - Sazali, Halimatussaadiah (Faculty of Applied Sciences, 2017)
Studies on qualitative phytochemical analysis and bioactivities of Carica papaya leaves were carried out. Leaves of C. papaya has been extracted using various of polar solvents which are methanol, chloroform and hexane. The results of leaves extract using methanol solvent showed the highest percentage of 7.13 %. Thin layer chromatography (TLC) shows a better component separation pattern at the ratio of 8:2, 7.5:2.5 and 8.5:1.5 in hexane and acetone solvent systems. The results of phytochemical analysis on methanol extract showed the presence of various chemical components such as flavonoids, saponins, glycosides, steroids, terpenoid, alkaloids, phenols and tannins. The results of antibacterial activity on selected bacteria using disc diffusion method showed the effect of inhibition on B. subtilis and S. typhi with inhibition diameter of 8.0 mm and 10.0 mm respectively. Antioxidant activity on C. papaya leaves extract was detected using bioautography of thin layer chromatography and the results showed the presence of antioxidant compound in each C. papaya leaves extract.